2010
DOI: 10.1007/s00425-010-1149-2
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive expression of CaSRP1, a hot pepper small rubber particle protein homolog, resulted in fast growth and improved drought tolerance in transgenic Arabidopsis plants

Abstract: Transient and long-term shortages of fresh water are major adverse environmental factors that cause dramatic reductions in crop production and distribution globally. In this study, we isolated a full-length CaSRP1 (Capsicum annuum stress-related protein 1) cDNA, which was rapidly induced by dehydration in hot pepper plants. The predicted CaSRP1 protein sequence exhibited significant amino acid identity to putative stress-related proteins and the small rubber particle protein (SRPP) found in rubber trees (Hevea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 49 publications
1
32
0
Order By: Relevance
“…Total RNA was treated with DNase I (Promega, Madison, WI) for 30 min, and then, first-strand cDNA was synthesized as described by Kim et al (2010). RT-PCR was performed using gene-specific primer sets (Supplemental Table S1).…”
Section: Protein Assaysmentioning
confidence: 99%
“…Total RNA was treated with DNase I (Promega, Madison, WI) for 30 min, and then, first-strand cDNA was synthesized as described by Kim et al (2010). RT-PCR was performed using gene-specific primer sets (Supplemental Table S1).…”
Section: Protein Assaysmentioning
confidence: 99%
“…For instance, the LDAP genes and their SRPP counterparts are strongly induced in some plants in response to abiotic stress (Sookmark et al, 2002;Priya et al, 2007;Kim et al, 2010;Seo et al, 2010;Fricke et al, 2013) as well as ectopic application of abscisic acid, as indicated by the Arabidopsis eFP Browser microarray database (Winter et al, 2007). LDs are also known to be involved in lipid metabolism associated with pathogen infection (Herker and Ott, 2012;Murphy, 2012), and biochemical studies have shown a significant increase in TAG and neutral lipids in plants subjected to heat, cold, drought, and salt stress (Mueller et al, 2015;Tarazona et al, 2015).…”
Section: A Role For Ldaps During the Plant Stress Responsementioning
confidence: 99%
“…In LDAP-disrupted plant lines, however, there were no significant decreases in neutral lipid content, although ldap3-1 and ldap3-2 mutant lines did show modest increases in neutral lipid abundance ( Fig. 3C Prior studies revealed that LDAP genes are strongly induced during abiotic stress responses in a variety of plant species (Sookmark et al, 2002;Priya et al, 2007;Kim et al, 2010;Seo et al, 2010;Fricke et al, 2013), and more recent studies have shown that neutral lipid content, particularly TAG, is increased in response to cold or heat (Mueller et al, 2015;Tarazona et al, 2015). Given that LDAPs target to LDs (Figs.…”
mentioning
confidence: 99%
“…The primer sets used in this study were FDH1 (forward, 59-ATGGCGATGAGG-CGTGTGGCATCT-39; reverse, 59-TTAGCGATACTGGGGTGCCAGTTCC-39), CaPR1 (forward, 59-CAGGATGCAACACTCTGGTGG-39; reverse, 59-ATCA-AAGGCCGGTTGGTC-39), CaPR10 (forward, 59-ATGGGTGCTTATACCTTT-ACTGAC-39; reverse, 59-TTAAACATAGACAGAAGGATTGG-39), CaDEF1 (forward, 59-CAAGGGAGTATGTGCTAGTGAGAC-39; reverse, 59-TGCAC-AGCACTATCATTGCATAC-39), AtPR1 (forward, 59-AGTATGGCTTCTCGT-TCACA-39; reverse, 59-GGAGCTACGCAGAACAACTA-39), AtPR4 (forward, 59-GCCATCTCATTGTTGACTACCAATTT-39; reverse, 59-ATCAATGGCC-GAAACAAGCA-39), and AtPDF1.2 (forward, 59-TGTTCTCTTTGCTGCTT-TCGACGC-39; reverse, 59-TGTGTGCTGGGAAGACATAGTTGC-39). Relative gene expression was normalized using pepper Actin (Kim et al, 2010) and Arabidopsis Ubiqutin5 (UBQ5; forward, 59-GTAGTGCTAAGAAGAGGAAGA-39; reverse, 59-TCAAGCTTCAACTCCTTCTT-39) as internal controls. Average expression was calculated from three experimental replicates.…”
Section: Rna Gel Blotting and Qrt-pcrmentioning
confidence: 99%